2002
DOI: 10.1083/jcb.200209011
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-induced TrkB activation down-regulates the K+–Cl− cotransporter KCC2 and impairs neuronal Cl− extrusion

Abstract: Pathophysiological activity and various kinds of traumatic insults are known to have deleterious long-term effects on neuronal Cl− regulation, which can lead to a suppression of fast postsynaptic GABAergic responses. Brain-derived neurotrophic factor (BDNF) increases neuronal excitability through a conjunction of mechanisms that include regulation of the efficacy of GABAergic transmission. Here, we show that exposure of rat hippocampal slice cultures and acute slices to exogenous BDNF or neurotrophin-4 produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
414
4
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(440 citation statements)
references
References 36 publications
19
414
4
3
Order By: Relevance
“…This view is supported by experimental evidence in which it was shown that following damage to afferents in the spinal cord, BDNF liberated by microglia activates trkB receptors leading to a KCC2 down-regulation and a depolarizing shift in GABAergic reversal potentials associated with pathological pain responses (Price et al, 2005;Lu et al, 2008). It has also been shown that experimentally induced interictal activity in hippocampal slices maintained in vitro, downregulates KCC2 mRNA and protein expression in CA1 pyramidal neurons, which leads to a reduced capacity for neuronal Cl − extrusion (Rivera et al, 2002(Rivera et al, , 2004Blaesse et al, 2009). Alterations in the balance of NKCC1 and KCC2 activity have also been identified in the subiculum and hippocampus of epileptic patients by Munoz et al (2007).…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%
“…This view is supported by experimental evidence in which it was shown that following damage to afferents in the spinal cord, BDNF liberated by microglia activates trkB receptors leading to a KCC2 down-regulation and a depolarizing shift in GABAergic reversal potentials associated with pathological pain responses (Price et al, 2005;Lu et al, 2008). It has also been shown that experimentally induced interictal activity in hippocampal slices maintained in vitro, downregulates KCC2 mRNA and protein expression in CA1 pyramidal neurons, which leads to a reduced capacity for neuronal Cl − extrusion (Rivera et al, 2002(Rivera et al, , 2004Blaesse et al, 2009). Alterations in the balance of NKCC1 and KCC2 activity have also been identified in the subiculum and hippocampus of epileptic patients by Munoz et al (2007).…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%
“…This downregulation may be mediated via trk receptors for growth factors whose ambient extracellular concentrations depend on neuronal activity (Rivera et al, 2002). Such a mechanism might operate in human epileptic tissue, but it remains unclear why only a minority of cells are affected.…”
Section: Does An Epileptic Brain Emerge From Developmental and Repairmentioning
confidence: 99%
“…Previous studies in the hippocampus suggested that BDNF mediated KCC2 down-regulation (Rivera et al, 2002;. Consequently, in our study we sought to examine whether increases in BDNF coincided with the decreases in KCC2 levels post-ligation.…”
Section: Increases In Bdnf Protein Levels In the Spinal Dorsal Horn Cmentioning
confidence: 99%
“…In the adult brain enhanced expression of both BDNF and its high-affinity TrkB receptors appear to predispose certain cortical areas to seizures (Binder et al, 2001). This BDNF-induced hyper-excitability may be at least in part due to the loss of GABA inhibition mediated by the TrkB-dependent down-regulation of KCC2 (Wardle and Poo, 2003;Rivera et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%